Pay-to-Win Loot Boxes and their impact on players’ experience - Hietamäki, Ville (My University, 2025)
This research investigates pay-to-win loot boxes and the impact they have on players’ experiences in video games. As the popularity of video games has been on the rise in the last two decades, the revenue generating methods have evolved alongside it. With the emergence of microtransactions we have seen plenty of different implementations of monetization methods, which include the pay-to-win microtransactions and pay-to-win loot boxes. Despite the prevalence of these microtransactions, they have received negative feedback, as the impact they can have on competitive gameplay is apparent. This thesis attempts to discover the perceptions of players to analyze and understand the players’ experiences towards these microtransactions and specifically pay-to-win loot boxes. This study employs a pre-gameplay questionnaire, a tailored demo game, and a post-gameplay questionnaire. The purpose of the employed game is to demonstrate the effects of loot boxes in a gameplay environment, mainly for the participants without previous experience on the subject. The purpose of the questionnaires is to inquire about players’ experiences, expectations, and the changes in them prior and post the gameplay. The results of the questionnaires will then be analyzed using mixed-methods analysis, as the questionnaires contain both quantitative and qualitative questions. The results showed that the participants’ experiences had no significant changes after the gameplay, and that their expectations as well as experiences prior to the game had been negative towards the pay-to-win loot boxes and the pay-to-win microtransactions. The main reason being the impact towards competitive gameplay, especially in the case of player-versus-player games, while the only positive insights on this type of microtransactions were directed towards single-player games, such as the presented demo game. These findings suggest that game developers should consider which types of microtransactions their games include, as the pay-to-win models can steer players away even before they have tried the games.
Keywords: Pay-to-win, Loot boxes, Microtransactions, Video games